2017
DOI: 10.1074/mcp.o116.065219
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach to Analyze the Aspirin-mediated Lysine Acetylome

Abstract: Aspirin, or acetylsalicylic acid is widely used to control pain, inflammation and fever. Important to this function is its ability to irreversibly acetylate cyclooxygenases at active site serines. Aspirin has the potential to acetylate other amino acid side-chains, leading to the possibility that aspirin-mediated lysine acetylation could explain some of its as-yet unexplained drug actions or side-effects. Using isotopically labeled aspirin-d3, in combination with acetylated lysine purification and LC-MS/MS, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 50 publications
0
39
1
Order By: Relevance
“…Another recent proteomic study by Tatham and co-workers used 3 H-labeled aspirin to identify sites of aspirin-mediated acetylation in HeLa cells by mass spectrometry [ 124 ]. In this approach, the use of tritiated aspirin results in a +3 Da mass shift relative to normal acetate and allows more accurate discrimination of aspirin-mediated acetylation versus endogenous acetylation.…”
Section: The Role Of Platelets In the Clotting Cascadementioning
confidence: 99%
“…Another recent proteomic study by Tatham and co-workers used 3 H-labeled aspirin to identify sites of aspirin-mediated acetylation in HeLa cells by mass spectrometry [ 124 ]. In this approach, the use of tritiated aspirin results in a +3 Da mass shift relative to normal acetate and allows more accurate discrimination of aspirin-mediated acetylation versus endogenous acetylation.…”
Section: The Role Of Platelets In the Clotting Cascadementioning
confidence: 99%
“…Although this electrostatic hypothesis is unconventional, it is not unreasonable. Pharmacological agents such as aspirin, the simplest aryl ester, can transfer acetyl groups directly to lysine residues of ϳ100 different proteins (12)(13)(14)(15). In general, the neutralization of a single lysine-⑀-NH 3 ϩ in a protein is expected to have a large effect on its overall net charge because proteins are predicted to have low values of net charge to begin with ("low" defined as Z between Ϫ10 and ϩ10) (16).…”
mentioning
confidence: 99%
“…The prolongation of the period before the onset of death related to malignancy was found to be approximately five years for esophageal, pancreatic, brain, and lung cancers, and was even higher for gastric, colon, and prostate cancers [2,37]. This effect of ASA is currently explained by its ability to acetylate proteins other than COX-1 [38]. Recently, it has been demonstrated that ASA also decreases the expression of the hypoxia-inducible factor 1alpha (HIF1α), a key regulator of genes that are involved in metabolism under hypoxic conditions and a major determinant of tumor cell stabilization [39,40].…”
Section: Discussionmentioning
confidence: 99%